Hubungan Kebiasaan Merokok Terhadap Kejadian Penyakit Gastritis di Kecamatan Suli Kabupaten Luwu Tahun 2024 - Asri, Muhammad; H, Hadija; S, Surahman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Smoking habits can cause gastric disorders under normal circumstances the stomach can survive the acidity of gastric juice, nicotine can prevent hunger so that a person becomes not hungry because of smoking, therefore it can increase stomach acid and can cause gastritis. The cause of gastritis is generally Hellcobacter pylori infection, gastritis caused by Hpylori infection is the main risk factor for peptic ulcer disease and its complications, as well as gastric cancer. The aim of this research is to ascertain how smoking behaviors relate to the prevalence of gastritis in Luwu Regency. This type of research is a quantitative research with an analytical descriptive research design with a cross sectional approach. With the total sampling technique, a sample of 30 respondents was obtained, independent variables of smoking habits, dependent variables of gastritis incidence. Data collection uses questionnaires. The chis-quare statistical test was used to look for relationships and test hypotheses. It is known that out of 30 respondents there are 1 respondent (3.3%) who smoke lightly and 10 respondents (33.3%) who smoke moderately, while there are 19 respondents (63.3%) who have heavy smoking behavior. It is known that out of 30 respondents, there are 2 respondents (6.7%) who suffer from mild gastritis and 12 respondents (40.0%) who suffer from moderate gastritis while those who experience severe gastritis are 16 respondents (53.3%). Based on the results of the statistical test from the chis-square test value, a value of p = 0.03 with a significant value of a = 0.05 indicates that H1 is accepted and H0 is rejected, meaning that there is a significant relationship between smoking behavior and the incidence of gastritis disease, meaning that it can be concluded that there is a relationship between smoking habits and the incidence of gastritis disease in Suli District, Luwu Regency in 2024.